FAKTOR YANG MEMPENGARUHI PREFERENSI KONSUMEN KEDAI KOPI MODERN DI BONDOWOSO - Mochamad Hafezd As'ad; Joni Murti Mulyo Aji (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2020)
In the modern era today, coffee consumption lifestyle started to develop and penetrated the community especially in urban areas. The rapid growth of coffee shops in Indonesia, could be seen as well in Bondowoso. The existence of city branding "Bondowoso Coffee Republic" has increasingly encouraged the emergence of modern coffee shops. This study aimed to determine: (1) the characteristics of modern coffee shop consumers in Bondowoso, (2) factors that influenced the preferences of modern coffee shop consumers. Research area was determined intentionally (purposive method), namely the urban area of Bondowoso Regency. The location of the study was conducted at modern coffee shops located in the City. The sampling method used was incidental sampling with a total of 120 respondents in 3 selected modern coffee shops. The results showed that: (1) there were several characteristics of modern coffee shop consumers in urban areas of Bondowoso consisting of male with a percentage of 77.5 percent and female of 22.5 percent, 66.67 percent of consumers had the intensity of drinking coffee as much as 3-4 cups per day, ( 2) formed 4 factors that influenced consumer preferences based on 15 variables, namely brand image, service, coffee and modernity.